Sports injury prevention: The role of the strength and conditioning coach - Talpey, S. W.; Siesmaa, E. J. (Strength and Conditioning Journal, 2017)
Prevention of sports injuries is a priority for sport stakeholders across the spectrum of training and competition. Achieving this objective requires a multidisciplinary approach with strength and conditioning coaches playing an important role in the process. When considering sports injury prevention strategies, the role of the strength and conditioning coach can extend beyond observing exercise technique and prescribing training to develop a robust and resilient athlete. This paper provides strength and conditioning coaches with a broad overview of the sports injury prevention process and outlines examples of how strength and conditioning coaches can work to promote and improve athlete safety.